(untitled) (Research, Society and Development, 2020)
The aim of this study was to perform a spatial analysis of fatal victims of traffic accidents among motorcyclists in the city of Teresina-PI. The database was provided for this study by the Municipal Health Foundation of Teresina, comprising all sources of traffic accident records in Teresina in 2014. It was evidenced that young male adults were the main victims accidents, with outcomes of 85.3% (fatal) and 81.6% (severe). Regarding the age group, the injured individuals were between 18 and 35 years old. Of the 1082 victims, 109 (10.07%) were fatal and 973 (89.93%) had a serious outcome. It was also observed that the motorcycle was the main means of transportation that contributed to the occurrence of these accidents, where 50.46% were fatal and 84.1% serious. The incidence of accidents with fatal victims in Teresina had a minimum latitude of -5.36 and a maximum longitude of -42.77. The highest concentrations of motorcycle fatalities occurred in the busiest avenues in Teresina: Miguel Rosa with BR 343 and BR 316, Av. Maranhão, Kennedy and Raul Lopes. In the analysis of the map, it was noticed that the busiest avenues tend to have a motorcycle cluster. The state or federal highways with free traffic and the areas close to roundabouts that have a cluster for “other means of transportation” are, respectively, automobiles and pedestrians. Therefore, studies like these serve as subsidies for actions and planning in city traffic, so that many lives are preserved.